2020
DOI: 10.1016/j.oceaneng.2019.106774
|View full text |Cite
|
Sign up to set email alerts
|

Safety-zone layout design for a floating LNG-Fueled power plant in bunkering process

Abstract: The use of natural gas (NG) as an energy source is increasing. This paper studies the safety-zone layout design of a floating power plant fueled by NG. Hazards from the unwanted release of liquefied NG (LNG) in bunkering or NG in operation always exist, and it is thus important to reduce the associated risk to an acceptable level. One engineering technique used to reduce this risk involves the design of a safety zone to prevent and minimize exposures that may occur during unwanted release of LNG or NG. Industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Lee et al [32] analyzed willingness to pay for replacing common fuels with LNG in the case of flour imports and found that consumers accept prices up to 36% higher than the average price. Park et al [33] studied the safety zone layout design of a floating power plant fueled by natural gas. They provided an example of a hybrid approach for LNG.…”
Section: General Reviewmentioning
confidence: 99%
“…Lee et al [32] analyzed willingness to pay for replacing common fuels with LNG in the case of flour imports and found that consumers accept prices up to 36% higher than the average price. Park et al [33] studied the safety zone layout design of a floating power plant fueled by natural gas. They provided an example of a hybrid approach for LNG.…”
Section: General Reviewmentioning
confidence: 99%
“…Some research studies have been conducted regarding the risks of LNG bunkering. These have mainly focused on the following three aspects: (1) safety zone evaluation [10][11][12][13][14][15][16][17][18][19][20][21][22], (2) risk assessment methodology and practice [23][24][25][26][27], and (3) emergency evacuation assessment [27,28]. Even though these studies have improved our understanding of LNG bunkering safety, none has quantified human errors in LNG bunkering.…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies have been conducted regarding the risks of LNG bunkering. These have mainly focused on the following three aspects: (1) safety zone evaluation [10][11][12][13][14][15][16][17][18][19][20][21][22],…”
Section: Introductionmentioning
confidence: 99%
“…These liquified gases are cryogenic liquids meaning that they are cooled down below about −150°C. Liquefied gas leakage from cargo containments or fuel tanks of ships, as well as during bunkering of liquefied gases to vessels or offshore power plants, is a potential risk (Paik et al 2020;Park et al 2020). Such leaks can adversely affect the structural integrity of stiffened steel plates used in ship hulls and offshore structures by embrittling them at cryogenic temperatures (Paik et al 2020).…”
Section: Introductionmentioning
confidence: 99%